Pembelajaran Akidah Akhlak Berbasis Metode Edutaiment Di Madrasah Aliyah Negeri (MAN) Wajo - Amaliyah Iqbal, Nabilah (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2022)
These developments in the world of education make education today no longer be reduced to a process of transfer of knowledge. Fun education also pays attention to human principles. Fun learning affects the teaching and learning atmosphere so that they can focus their attention fully while studying so that their time on task is high. This study aims to provide an overview of the planning and learning outcomes of aqidah morals with the edutainment method at MAN WAJO. This study uses a qualitative method with a case study approach that only focuses on the edutainment strategy of learning aqidah akhlak in Madrasah Aliyah Negeri Wajo. The results of this study, the first planning of learning strategies for aqidah morals with the edutainment method at MAN WAJO, learning with the edutainment method (fun) for students so that they do not experience boredom and boredom. In its application, students are given the freedom to be creative, so it is easier to recognize and accept material according to their creativity. Second, the results of the moral aqidah learning strategy using the edutainment method strategy showed that there were three aspects that were assessed from the results of the edutainment method 1) cognitive aspects, students were easy to accept ongoing lessons, 2) affective aspects, students showed enthusiasm and enthusiasm in learning. learning, 3) psychomotor aspects, students learn while playing in class and outside the classroom.